Production of 13C-labeled docosahexaenoic acid from heterotrophic marine microorganisms Aurantiochytrium mangrovei and Crypthecodinium cohnii enabling fluxomic applications - Buscaglia, Manon; Gouriou, Bastian; Asquoët, Yoann; Le Goïc, Nelly; Le Grand, Fabienne; Hachem, Mayssa; Soudant, Philippe (Frontiers in Bioengineering and Biotechnology, 2025)
Docosahexaenoic acid (DHA, 22:6n-3) is the predominant polyunsaturated fatty acid in the human brain and eyes, playing a crucial role in vision and cognitive development. DHA deficiency has been associated with ocular diseases, such as macular degeneration and glaucoma, as well as neurodegenerative disorders. Since the human body has a limited ability to synthesize DHA from its precursor, alpha-linolenic acid (ALA, 18:3n-3), targeted DHA supplementation is essential for these patients. To investigate DHA metabolism and integration, researchers commonly use stable (2H,13C) or radioactive (3H,14C) isotopes, which are expensive and not widely accessible, restricting the scope and duration of studies. This study aimed to develop a sustainable method for biosynthesizing uniformly labeled 13C-DHA by culturing the heterotrophic protists Aurantiochytrium mangrovei and Crypthecodinium cohnii with 13C-glucose. The major fatty acids (FA) of A. mangrovei included 16:0, 22:5n-6 (DPA), and DHA, with DHA accounting for 50.5% ± 4.9% of the total FA. Gas Chromatography-Mass Spectrometry (GC-MS) analysis revealed a13C-enrichment of DHA at 96.7% ± 0.4% after the effective High Performance Liquid Chromatography (HPLC) purification. The predominant FA of C. cohnii were 12:0, 14:0, 16:0, and DHA, with DHA representing around 27% of the total FA and exhibiting a13C-enrichment of 86.3% ± 1.6%. Based on FA content, A. mangrovei showed a balanced distribution of neutral and polar lipids, with DHA predominantly in the polar fraction (57.8% ± 3.1%), whereas C. cohnii exhibited a predominance of neutral lipids (82.4% ± 0.3%), which contained the majority of its DHA (57.5% ± 1.0%).